Ecclesiastical normativity and particularism in the New World: the regulation of baptism in the Synod of Salvador da Bahia (1707) and its practice in the Freguesia of Fortaleza (18th century) - Cabral, Gustavo César Machado (História do Direito, 2021)
This paper aims to contribute with the study of ecclesiastical normativities in Portuguese America, mainly after the enactment of the First Constitutions of the Archbishopric of Bahia (1707). By analyzing baptism, which is regarded as the first Catholic sacrament, this text focuses on the creation of norms for particular spaces and how this process incorporates juridical and theological traditions. At the same time, the text confronts this analysis with the baptismal records of the freguesia of Fortaleza during the 18th century, in order to verify if this formal regulation actually was put into practice.